Perbandingan Efektifitas Protective Coating, Silica Fume dan Semen Tipe II Terhadap Pengaruh Klorida dan Sulfat pada Beton - Herdiansah, Yudi; Sulaeman, Agus; Destianto, Anto (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2023)
Concrete that is in a surrounding with high sulfate and chloride levels can affect durability of concrete. Numerous technologies that might be often used include: protecting coating, addition of silica fume to concrete mix, and type II cement. Consequently, the intention of this have a look at was to examine effectiveness of shielding coatings, the addition of silica fume to the concrete blend, and the usage of kind II cement to grow the sturdiness of concrete uncovered to chlorides and sulfates. The specimens were made in 4 variations; cement type I specimens without protection, cement type I specimens with coating, cement type I specimens with silica fume, and cement type II without protection. The specimens were immersed in a solution of chloride and sulfate for 14 days, 28 days, 42 days, and 56 days. The study was carried out by testing the compressive strength, chloride content, chloride infiltration, visual analysis, and change of length. The results showed that protective coating had resistance to chloride and sulfate, the addition of silica fume to cement type I provided resistance to chloride but did not to sulfate, while the use of cement type II provided resistance to sulfate but did not provide chloride.